Improved Charger for Electric Vehicle (International Journal of Innovative Research in Engineering & Management, 2022)
The numbers of electric automobiles are quickly increasing. Recharging facilities for electric  vehicles are also becoming more frequent. This article  examines the present state of rechargeable batteries, charge  power levels, including charging techniques for electric  cars, as well as their application. There are two types of  off-board or on charging systems with or without dual  power flow. The use of unidirectional charging reduces the  amount of hardware required and simplifies connecting  concerns. Battery - based energy injection back to the grid  is made possible through bidirectional charging. Since of  weight, space, or cost limits, most on-board chargers limit  power. To circumvent these issues, they may be  incorporated with the electric drive. This paper produces a  different phase 230volt off boards charger utilizing CC,  CV, or CC-CV charging techniques, as well as simulation  results comparing the aforementioned approaches using a  3.2volt, 10AH battery pack in MATLAB.
Keywords: Battery; Electric; MATLAB; Vehicle